Pengaruh Work Life Balance dan Gaya Kepemimpinan terhadap Kinerja Karyawan di Direktorat Jenderal Badan Peradilan Militer dan Peradilan Tata Usaha Negara Mahkamah Agung RI - Intan Novindriyani; Purwatiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of Work Life Balance (WLB) and Leadership Style on Employee Performance at the Directorate General of Military Courts and Administrative Courts of the Supreme Court of the Republic of Indonesia. The background of this research is based on the importance of balancing work and personal life, as well as the role of effective leadership in improving the performance of government agency employees. This research uses a quantitative method with an associative approach. The sample of this study consists of the entire population of 94 employees using saturated sampling technique. Data was collected through questionnaires and analyzed using SPSS, including validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that Work Life Balance has a positive and significant impact on Employee Performance, indicating that a balance between work and personal life positively affects job productivity and satisfaction. Leadership Style also has a positive and significant impact on Employee Performance, where good leadership can motivate and facilitate employees in achieving organizational goals. Simultaneously, both variables significantly influence employee performance in the organization. This study provides important implications for organizational management, suggesting that implementing a good Work Life Balance and an appropriate leadership style can optimally improve employee performance.